2016
DOI: 10.1002/wrna.1373
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules targeting viral RNA

Abstract: Highly conserved noncoding RNA (ncRNA) elements in viral genomes and transcripts offer new opportunities to expand the repertoire of drug targets for the development of antiinfective therapy. Ligands binding to ncRNA architectures are able to affect interactions, structural stability or conformational changes and thereby block processes essential for viral replication. Proof of concept for targeting functional RNA by small molecule inhibitors has been demonstrated for multiple viruses with RNA genomes. Strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
143
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 120 publications
1
143
0
Order By: Relevance
“…As these IRESs are found in medically and economically important pathogens, they raise possibilities as drug targets (Davis and Seth, 2010; Dibrov et al, 2012; Hermann, 2016) and are useful tools for exploring both IRES function and fundamental principles of translation initiation, so it is important that we fully understand how they work. Therefore, we re-examined the mechanism used by the HCV IRES with approaches designed to complement previous biochemical and structural studies.…”
Section: Introductionmentioning
confidence: 99%
“…As these IRESs are found in medically and economically important pathogens, they raise possibilities as drug targets (Davis and Seth, 2010; Dibrov et al, 2012; Hermann, 2016) and are useful tools for exploring both IRES function and fundamental principles of translation initiation, so it is important that we fully understand how they work. Therefore, we re-examined the mechanism used by the HCV IRES with approaches designed to complement previous biochemical and structural studies.…”
Section: Introductionmentioning
confidence: 99%
“…[7a, 8] In studies targeting r(CUG)-repeat sequences in 2015, Disney et al tested a drug-like, RNA-biased library of bis-benzimidazoles and similar core structures and found that bioactive molecules had statistically significant differences in topological polar surface area (tPSA) as well as hydrogen bond acceptors (HBA) and donors (HBD). [9] Inspired by this previous work and the recent surge in discoveries of biologically active RNA-targeting ligands, [10] we proposed to more broadly analyze the key guiding principles for specific RNA-targeting. In this work, we report the discovery of distinct physicochemical, structural, and spatial properties of RNA-targeted bioactive ligands, which are expected to facilitate the rapid discovery of RNA-targeted chemical probes and subsequent evaluation of the therapeutic potential of non-ribosomal RNAs.…”
mentioning
confidence: 99%
“…First, we gathered reports from reviews [10-11] and recent primary literature that described organic small molecule probes for non-ribosomal RNAs with evidence of both in vitro binding and target engagement in cell culture or animal models (SI-1). To focus on small organic molecules, peptides and oligonucleotides were omitted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2629 In contrast to synthetic oligonucleotides, which are limited to targeting single-stranded sequences, small molecules offer the opportunity for three-dimensional structure-based targeting. 3032 Many unanswered questions remain, however, regarding both the small molecule properties and the RNA structures that allow selective interactions, and insights into this relationship would facilitate both RNA-targeted drug discovery and the development of small molecule probes for RNA structure and function.…”
Section: Introductionmentioning
confidence: 99%